2009
DOI: 10.1083/jcb.200807155
|View full text |Cite
|
Sign up to set email alerts
|

Dynein light chain regulates axonal trafficking and synaptic levels of Bassoon

Abstract: Bassoon and the related protein Piccolo are core components of the presynaptic cytomatrix at the active zone of neurotransmitter release. They are transported on Golgi-derived membranous organelles, called Piccolo-Bassoon transport vesicles (PTVs), from the neuronal soma to distal axonal locations, where they participate in assembling new synapses. Despite their net anterograde transport, PTVs move in both directions within the axon. How PTVs are linked to retrograde motors and the functional significance of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
93
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 63 publications
(119 reference statements)
3
93
0
Order By: Relevance
“…Higher apparent affinity of DYNLL binding to dimeric protein fragments was first noted by studying DYNLL2 and myoVa interactions (2) and later attributed to avidity (15). This hypothesis questioned the original proposal of heterodimeric cargo adapter role of DYNLL on dynein and myoVa motor complexes (6,7,21,(55)(56)(57)(58).…”
Section: Fine-tuning Of Affinities Is Achieved Through Diversity Of Bmentioning
confidence: 85%
“…Higher apparent affinity of DYNLL binding to dimeric protein fragments was first noted by studying DYNLL2 and myoVa interactions (2) and later attributed to avidity (15). This hypothesis questioned the original proposal of heterodimeric cargo adapter role of DYNLL on dynein and myoVa motor complexes (6,7,21,(55)(56)(57)(58).…”
Section: Fine-tuning Of Affinities Is Achieved Through Diversity Of Bmentioning
confidence: 85%
“…Its crucial role has been demonstrated in several organisms, including Drosophila, in which null mutations result in embryonic lethality (Dick et al, 1996). DLC associates with a wide variety of proteins, including neuronal nitric oxide synthase (nNOS) (Jaffrey and Snyder, 1996), gephyrin (Fuhrmann et al, 2002), bassoon (Fejtova et al, 2009), the proapoptotic factor Bim (Puthalakath et al, 1999), transcriptional factors Swallow (Schnorrer et al, 2000) and Trps1 (Kaiser et al, 2003), viral proteins (Raux et al, 2000) and p53 binding protein 1 (Lo et al, 2005). Because DLC is a light chain of motor proteins, its role in trafficking has been widely assessed.…”
Section: Introductionmentioning
confidence: 99%
“…GKAP also interacts with the dynein light chain [DLC, also known as LC8 and DYNLL (Naisbitt et al, 2000)]. DLC is an essential component of the dynein and myosin V molecular motors (Benashski et al, 1997), but is also found in numerous other complexes (Fejtova et al, 2009;Fuhrmann et al, 2002;Jaffrey and Snyder, 1996;Lo et al, 2005;Puthalakath et al, 1999;Raux et al, 2000;Schnorrer et al, 2000). Thus, in addition to its role in transport as a molecular motor light chain (Lee et al, 2006;Navarro et al, 2004;Schnorrer et al, 2000), DLC could be an ordered hub protein as well, promoting the oligomerization and ordering of the natively disordered monomeric proteins with which it interacts (Benison et al, 2006;Nyarko et al, 2004;Wang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%